What makes travel 'local': Defining and understanding local travel behaviour - Manaugh, Kevin; El-Geneidy, Ahmed (Journal of Transport and Land Use, 2012)
In recent years, land use and transportation planning priorities have shifted from issues of mobility to focus on the capacity of neighbourhoods to provide opportunities to live, work, shop, and socialize at the local scale. This research explores a sample of households from Montreal, Quebec, Canada that engaged in multiple trip purposes on the same day and measures the effects of household, individual, and trip characteristics on their travel behaviour, especially the localization of these trips. A new measure to understand the spatial dispersal of actual activity space of each household is proposed while controlling for distance traveled. The findings show that levels of regional and local accessibility have different effects on this new index. These effects do vary with households size and socio-demographic factors. This study helps transportation professionals who are aiming to develop policies to localize household travel patterns through land use and transportation coordination at the neighbourhood and regional scale. Implications for social equity and exclusion are also explored.